Novel PRPS1 gain‐of‐function mutation in a patient with congenital hyperuricemia and facial anomalies. Issue 10 (25th July 2017) - Porrmann, Joseph; Betcheva‐Krajcir, Elitza; Di Donato, Nataliya; Kahlert, Anne‐Karin; Schallner, Jens; Rump, Andreas; Schröck, Evelin; Dobritzsch, Doreen; Roelofsen, Jeroen; van Kuilenburg, André B. P.; Tzschach, Andreas
Abstract : Phosphoribosylpyrophosphate synthetase (PRPPS) superactivity (OMIM 300661) is a rare inborn error of purine metabolism that is caused by gain‐of‐function mutations in the X‐chromosomal gene PRPS1 (Xq22.3). Clinical characteristics include congenital hyperuricemia and hyperuricosuria, gouty arthritis, urolithiasis, developmental delay, hypotonia, recurrent infections, short stature, and hearing loss. Only eight families with PRPPS superactivity and PRPS1 gain‐of‐function mutations have been reported to date. We report on a 7‐year‐old boy with congenital hyperuricemia, urolithiasis, developmental delay, short stature, hypospadias, and facial dysmorphisms. His mother also suffered from hyperuricemia that was diagnosed at age 13 years. A novel PRPS1 missense mutation (c.573G>C, p.[Leu191Phe]) was detected in the proband and his mother. Enzyme activity analysis confirmed superactivity of PRPP synthetase. Analysis of the crystal structure of human PRPPS suggests that the Leu191Phe mutation affects the architecture of both allosteric sites, thereby preventing the allosteric inhibition of the enzyme. The family reported here broadens the clinical spectrum of PRPPS superactivity and indicates that this rare metabolic disorder might be associated with a recognizable facial gestalt.